1974
DOI: 10.1038/bjc.1974.72
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Urethane Induced Lung Adenomata by Autosensitized Lymphocytes

Abstract: The present work investigates the influence of autosensitized lymphocytes on the carcinogenic response of the host. Urethane treated SWR mice received 6 fortnightly injections of lymphocytes sensitized in vitro against syngeneic fibroblasts. An increased incidence of lung adenomata was found in these mice compared with controls injected with unsensitized lymphoid cells or with lymphoid cells sensitized against unrelated transplantation antigens. Autosensitized lymphocytes also modified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Since autosensitized lymphocytes augmented the number of urethane-induced lung adenomas, Levo et al (1974) suggested that the host immune system was inadequately responsive, the effect being systemic rather than local. The possibility that immunosuppression by urethane could be counteracted by a-irradiation, and so lead to reduced adenoma formation, was considered by Brightwell and Heppleston (1973).…”
Section: Discussionmentioning
confidence: 99%
“…Since autosensitized lymphocytes augmented the number of urethane-induced lung adenomas, Levo et al (1974) suggested that the host immune system was inadequately responsive, the effect being systemic rather than local. The possibility that immunosuppression by urethane could be counteracted by a-irradiation, and so lead to reduced adenoma formation, was considered by Brightwell and Heppleston (1973).…”
Section: Discussionmentioning
confidence: 99%
“…With in vitro sensitization, animal immunotherapy trials showed that when these sensitized cells were mixed with live tumor cells and injected locally, they sometimes had an enhancing effect on the tumor growth [22,7,17,11], but if given IV they were effective in preventing the tumor growth [21,8]. The in vitro-sensitized lymphocytes were able to prevent recurrence of tumors when the primary tumor was removed, and this improved the survival by 40%.…”
Section: Introductionmentioning
confidence: 99%